Land management - Awange, Joseph (2018)
© Springer International Publishing AG 2018. Land provides the base upon which social, cultural and economic activities are undertaken and as such is of significant importance in environmental monitoring. Social, cultural and economic activities have to be planned and managed in such a way that the sustainable use of land resources is enhanced. Sustainable land use ensures that economic and socio-cultural activities do not benefit at the expense of the environment (see Sect. 13.5). Monitoring of changes in land through indicators could help in policy formulation and management issues for the betterment of the environment. Some of the vital indicators for land management include vegetation, soil quality and health, biosolids and waste disposed on land, land evaluation, land use planning, contaminated land, integrity of the food supply chain, mine closure completion criteria, and catchment management, in particular water balance, salinity, eutrophication, and riparian/wetland vegetation. This chapter presents the possibility of using GNSS satellites to enhance the monitoring of some of these indicators.